Research Trends in Teaching Materials to Improve Computational Thinking Skills: A Bibliometric Analysis from 2021 to 2025 - Aditya Saputra Dewa; Edi Kurniawan; Bambang Subali; Ellianawati (Journal of Pedagogy and Education Science, 2026)
The development of critical thinking as a key 21st-century competency is closely linked to computational thinking (CT), which requires systematic support through appropriate teaching materials. This study aims to analyse research trends in CT teaching materials published between 2021 and 2025 using a systematic review with a bibliometric approach following PRISMA guidelines. Data were collected from Crossref, Google Scholar, Scopus, and Semantic Scholar, resulting in 68 selected articles from an initial pool of 2,050 publications, which were analysed through content analysis and bibliometric mapping using VOSviewer. The findings reveal a significant increase in CT teaching material research in the post-pandemic period, particularly in 2023, with a predominance of empirical and research and development (R&D) studies. Most studies focus on computer science contexts, elementary education, and interactive digital teaching materials, indicating that CT is often positioned as an initial technical competency. In contrast, CT teaching materials for non-computer science subjects, other educational levels, and non-digital or unplugged contexts remain underexplored. Furthermore, existing research primarily emphasises product development and short-term effectiveness, while longitudinal studies examining the sustainability of CT learning outcomes are still limited. These findings highlight the need for pedagogically grounded, context-responsive, and interdisciplinary CT teaching materials, as well as future research employing longitudinal designs to support the equitable and sustainable development of CT as a core competence in 21st-century education.